1988
DOI: 10.1302/0301-620x.70b3.3372564
|View full text |Cite
|
Sign up to set email alerts
|

Joint laxity in idiopathic adolescent scoliosis

Abstract: Joint laxity was quantified by measuring the distance from the thumb tip to the forearm during passive apposition in 500 normal Southern Chinese women. Joint laxity was found to have a normal distribution throughout the population and to decrease with age. When 109 Chinese girls with idiopathic adolescent THE JOURNAL OF BONE AND JOINT SURGERY REFERENCES Beighton P, Solomon L, Soskolne CL. Articular mobility in an African population. Ann Rheum Dis 1973:32:413-8. Beighton PH, Horan Fl'. Dominant inheritance in f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
18
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 12 publications
4
18
0
1
Order By: Relevance
“…Using the Beighton score to determine laxity, the authors found a relationship between scoliosis and GJL [8]. This finding is also supported by the studies conducted by other authors [3,23].…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…Using the Beighton score to determine laxity, the authors found a relationship between scoliosis and GJL [8]. This finding is also supported by the studies conducted by other authors [3,23].…”
Section: Introductionsupporting
confidence: 62%
“…A number of studies suggest individuals with generalized joint laxity (GJL) are at an increased risk for musculoskeletal injury [3,6,7,14,19,23]. Several studies for different abnormalities have tried to establish this correlation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Auch sie können in variablen Kombinationen und Schweregraden vorliegen und prinzipiell jede "bindegewebige" Körper- [1,2,4,9,11,12,31,37,39,45,67,72] [63].…”
Section: Klinik Der Begleitmanifestationenunclassified
“…Interestingly, this protective action of dancing appears to be in complete contradiction with the results reported by Warren et al 11 McMaster et al 16,17 believe that the increased physical activities may possibly protect against AIS by involving neuromuscular feedback mechanisms common to all joints. 21 Th e latter is considered by many 22,23 as an important risk factor for the progression of scoliosis. 21 Th e latter is considered by many 22,23 as an important risk factor for the progression of scoliosis.…”
Section: Resultsmentioning
confidence: 99%